Phenomenological Account of Religious Experience - Donny Gahral Adian (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2011)
History of philosophy is built upon rigid discrimination between various human experiences. Human experiences are divided mainly into two major experiences: Perceptual and intelectual. Perceptual experience is deined by empiricism as an aposteriori experience of empirical sensations. Meanwhile, rationalism claims that the only acceptable experience is apriori experience of intelectual object (natural laws, mathematical equations and logical operations). There is no other experience outside those two philosophical account of experiences. All other experiences must be subsumed either within perceptual or intelectual experience.